COVID-19 home remedy consumption and perceived effectiveness among adult population in Brunei Darussalam: a PLS-SEM approach - Siti Nurzaimah Nazhirah Zaim; Deeni Rudita Idris; Hanif Abdul Rahman (BMC, 2024)
Abstract Background The Coronavirus Disease 2019 (COVID-19) caused by SARS-CoV-2 affects the respiratory system and causes severe acute respiratory infections. Several cultures have influenced the use of home remedies to ease mild symptoms of COVID-19 sometimes alongside conventional medicine. The aim of this study was to investigate the usage of COVID-19 home remedies among the adult population in Brunei. Methods The study design was a cross-sectional study using an online survey and distributed nationwide. The statistical analysis of the data included descriptive statistics describing the sociodemographic characteristics of the respondents, their experience with COVID-19 infection, consumption of general home remedies and COVID-19 home remedy, their practice of COVID-19 home remedy use, and their attitude towards the general use of home remedy. Sub-group analysis including Pearson's chi-square test and Fisher's exact test was computed for the variables in relation to the COVID-19 home remedy use and the perceived effectiveness of the types of home remedy. Multivariate analysis including Partial Least Squares Structural Equation Modelling (PLS-SEM) was applied to determine the correlations between the factors and outcomes measured. P-value less than 0.05 is considered statistically significant. Results There was a total of 864 eligible responses included in the study. The primary findings showed COVID-19 home remedy was used by 72.2% of the study participants. Most frequently used types of COVID-19 home remedy were cloves (37%), lemon (37%), and honey (23%). There was an infrequent usage of coconut (4.6%), eucalyptus oil (3.7%), habbatussauda (3.5%), traditional/ herbal cough syrup (2.4%), and turmeric (2.2%). The PLS-SEM demonstrated that 'Experience' appears to be a central endogenous variable that affects the decision on the use of COVID-19 home remedy. This relationship is mediated by 'Safety', 'Source', and 'Opinion' which have significant contributions to the outcome, accounting for 98.2% of the variance explained (R-square = 0.982). Conclusions The outcome of this study establishes the baseline prevalence of COVID-19 home remedy consumption among Bruneian residents and compared the previous study on Brunei's general use of traditional medicine. The present findings could help nurses and other healthcare professionals in Brunei understand the practice of Bruneian adults on the consumption of home remedies for COVID-19.